ANALISIS TENTANG NILAI-NILAI MORAL DALAM TRADISI MANDI SAMPAT PADA UPACARA PERKAWINAN MASYARAKAT MELAYU DI KELURAHAN TEBING KECAMATAN TEBING KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Ardhiansyah, Tri; Arianto, Jumili; ', Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by one of the traditions in the Malay community marriage ceremony, which is usually called Mandi tradition Sampat. The existence of the tradition of bathing sampat are currently conducted in the marriage ceremony as a cornerstone value for society wearer. The problems in this study is whether there is a Moral Values in the tradition of the nuptial Mandi Sampat Malay community in the Village Of Tebing Sub District Karimun Province Of Kepulauan Riau?. The purpose of this study was to determine the Moral Values contained in Mandi Sampat tradition in wedding ceremonies Malay community. The population in this study is the whole community in the Village of tebing married as many as 1,383 families . In the opinion of Earl Babbie (Prijana, 2005), that in order to understand the samples that were relevant in qualitative research is